3q29 microdeletion syndrome: Cognitive and behavioral phenotype in four patients. Issue 12 (24th September 2013) - Città, Santina; Buono, Serafino; Greco, Donatella; Barone, Concetta; Alfei, Enrico; Bulgheroni, Sara; Usilla, Arianna; Pantaleoni, Chiara; Romano, Corrado
Abstract The 3q29 microdeletion syndrome is a rare, recurrent genomic disorder, associated with a variable phenotype, despite the same deletion size, consisting in neurodevelopmental features, such as intellectual disability (ID), schizophrenia, autism, bipolar disorder, depression and mild facial morphological anomalies/congenital malformations. A thorough neuropsychiatric evaluation has never been reported in patients with such syndrome. We analyzed the clinical phenotype of four individuals with 3q29 microdeletion syndrome, with special emphasis on the cognitive and behavioral assessment, in order to delineate the neuropsychiatric phenotype related to this condition. We assessed these patients with standardized scales or checklists measuring the cognitive (WISC III or LIPS‐R), behavioral (CBCL) and adaptive (VABS) performances. An accurate evaluation in our sample highlights different degrees of ID, variable behavioral disorders, and a preservation of communicative skills among remaining adaptive areas, as the neuropsychiatric hallmark of 3q29 microdeletion syndrome. © 2013 Wiley Periodicals, Inc.